Exploring the Determinants of Operating Room Utilization: A Scoping Review of Influential Factors in Surgical Efficiency - Chumairah, Isma Sari; Basabih, Masyitoh (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Optimal utilization of the operating room (OR) is a crucial element in improving the efficiency of surgical services and hospital performance. This scoping review aimed to identify and map the factors influencing OR utilization based on recent scientific literature. We conducted a scoping review using the Population–Concept–Context (PCC) framework and reported it according to the PRISMA-ScR guidelines. We systematically searched PubMed, Scopus, and ScienceDirect for articles published between 2015 and 2025. Eligible studies were screened, and information on study characteristics and reported determinants of OR utilization was extracted and summarized descriptively. Forty studies were included. The reported determinants clustered into two broad domains: patient-related factors including age, Body Mass Index (BMI), American Society of Anesthesiologists (ASA) status, medical history, preoperative readiness, and financial conditions; and hospital-related factors including scheduling systems, waiting times, staff preparedness, resource availability, Post-Anesthesia Care Unit (PACU) and Intensive Care Unit (ICU) bed capacity, procedure complexity, and technology utilization. Across different settings, hospital and organizational factors showed a more consistent association with OR utilization than patient characteristics. The findings suggest that how ORs are managed and coordinated matters more for utilization than who the patients are. Strengthening scheduling, teamwork, and operational processes may therefore be key to improving OR utilization.